Identifying harm to the best efforts Internet - J. Scott Marcus; Martin Waldburger (International Telecommunications Society (ITS), 2015)
How are regulators to ensure that public Internet access services (continue to) provide good service to consumers, despite possible incentives on the part of network operators to act otherwise? Many express concerns that Internet traffic management and prioritisation might somehow motivate network operators to degrade non-prioritised traffic, thus turning the best efforts Internet (however defined) into a “dirt road” of poor capacity and quality. National regulators might well be obliged in the near future to assess whether this is in fact the case. How realistic is this fear? How are regulators to make this determination in practice? What pragmatic considerations come into play?
Keywords: 330